Research methodology and practical issues relating to the conduct of a medical device registry. (October 2019) - Bisdas, Theodosios; Bohan, Patrick; Lescan, Mario; Zeebregts, Clark J; Tessarek, Jörg; van Herwaarden, Joost; van den Berg, Jos C; Setacci, Carlo; Riambau, Vincent
Background: The postmarket research goal is to assess "generalizability" or "external validity" to see if the early results of clinical trials with investigational devices are reproducible in everyday practice in the real world and the longer term. Registries have an important but ambivalent role in achieving this goal. Methods: Although registries are common, in practice they follow the regulatory processes that appear designed primarily for pharmaceutical clinical trials and confirmatory studies. We review the literature to assess different definitions and the role of registries in the hierarchy of scientific evidence. We analyze common characteristics affecting registry design, implementation, and governance as well as safety reporting and off-label use while describing the experience of setting up an international, prospective registry for an endovascular device used to treat abdominal aortic aneurysms. Results: Key areas in which to distinguish registries from trials are as follows: eligibility, setting (patients and institutions), device configurations and iterations, the use of design and quality "spaces, " a focus on systematic quality checks (rather than source data monitoring), open-ended follow-up, flexibility in the definition of end points and sample sizes, data sharing, and publishing commitments. Conclusion: Both clinical trials and registries are essential and complementary research methods and the strengths and weaknesses of each need to be recognized. The specific characteristics of registry research deserve to be acknowledged and safeguarded in the regulations governing clinical investigations with medical devices.